Convict Depot Carrera Isle. Trinidad - (:unkn) unknown (Muir Marshall and Co.,[Trinidad and Tobago], 2011)
The postcard shows Carrera Island, referred to as Convict Depot because during the 1800s prisoners were carried to the island to quarry limestone for road building. In 1877, a prison was constructed, today the island remains a prison island. This postcard which is postmarked 1908, is addressed to F.C. White of Connecticut, United States of America and affixed is a one cent United States postage stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Islands--Trinidad and Tobago; 1908; Prisons--Trinidad and Tobago; Carrera Island